Partial Tracheal Defects Closure using Glutaraldehyde-Treated Autologous Pericardium - Yoshida, Shuhei; Matsumoto, Isao; Saito, Daisuke; Tanaka, Yusuke; Takemura, Hirofumi; Oi, Akishi (The Thoracic and Cardiovascular Surgeon, 2022)
Background The usefulness of autologous pericardium treated with glutaraldehyde (GA) for tracheal defect closure is unknown. This study preliminarily evaluated whether a GA-treated autologous pericardial graft can effectively close tracheal defects in a beagle model.Methods Defects of 10 mm × 10 mm were created on the trachea of 10 beagles and divided into a GA-treated group (n = 5), with tracheal reconstruction using GA-treated pericardium, and control group (n = 5), using fresh pericardium. Repair sites were evaluated through bronchoscopy and histology. Blood flows on graft were measured using laser Doppler technique on postoperative days (PODs) 0, 4, 7, 14, 28, and 56. Repair sites were histologically evaluated on POD 56. In addition, GA-treated pericardia of three other beagles were histologically evaluated 12 months postoperatively, for long-term follow-up.Results All animals survived; none developed anastomotic insufficiency. The mean suturing time and frequency of additional suture were significantly shorter and lower in the GA-treated group than in the control group (p = 0.002, 0.004). All animals in the control group exhibited graft contraction, whereas the GA-treated group healed with most graft residual and reepithelialization in the bronchoscopic and histological findings (p = 0.01, 0.004). Further, all long-term GA-treated pericardia of three beagles were confirmed as residual grafts with reepithelialization, without contraction, at 12 months postoperatively. Blood flows on graft using laser Doppler technique in the GA-treated group were detected at POD 14 or thereafter.Conclusion GA-treated pericardium was easier to handle and provided favorable scaffolding, without graft contraction, compared with the nontreated pericardium at short- and long-term follow-up.
Keywords: trachea; pericardium; experimental